Strategies for Rapid Identification of Acinetobacter baumannii Membrane Proteins and Polymyxin B’s Effects - Lu, Yun; Hu, Xinxin; Nie, Tongying; Yang, Xinyi; Li, Congran; You, Xuefu (Frontiers in Cellular and Infection Microbiology, 2021)
Acinetobacter baumannii, especially multi-drug resistant Acinetobacter baumannii, is a notable source of pressure in the areas of public health and antibiotic development. To overcome this problem, attention has been focused on membrane proteins. Different digestion methods and extraction detergents were examined for membrane proteome sample preparation, and label-free quantitative and targeted proteome analysis of the polymyxin B induced Acinetobacter baumannii ATCC 19606 membrane proteome were performed based on nano LC-MS/MS. Ultracentrifugation of proteins at a speed of 150,000×g, digestion by trypsin, filter-aided sample preparation and detergents such as lauryldimethylamine-N-oxide were proved as a fast and effective way for identification of membrane proteome by nano LC-MS/MS . Upon treatment with polymyxin B, expression levels of 15 proteins related to membrane structure, transporters, cell surface and periplasmic space were found to be significantly changed. And targeted proteome was also used to confirm these changes. A relatively rapid membrane proteome preparation method was developed, and a more comprehensive view of changes in the Acinetobacter baumannii membrane proteome under polymyxin B pressure was obtained.